The Scottish experience of devolution and secession referenda - Harvey, Malcolm (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
Consulting and engaging with the public has become vogue in recent years.  The United Kingdom, without a codified constitution, has utilised the referendum to decide upon constitutional issues, with the vote to leave the European Union in June 2016 the most recent of these.  This article explores the Scottish experience of referendums, examining the failed devolution referendum of 1979, the reversal of this decision in 1997, and the independence referendum of 2014, in which Scots, apparently decisively, voted to remain in the UK.  This article argues that, though on each occasion political considerations rather than principle led to the use of referendums, there are lessons to be learned from each, both for proponents of direct democracy and for campaigners and activists in similar cases.
Keywords: Scotland; Referendums; Devolution; Independence